Comparative analysis of ear-hole closure identifies epimorphic regeneration as a discrete trait in mammals - Thomas R. Gawriluk (Nature Portfolio, 2016)
The extent to which mammals and other vertebrates share similar mechanisms of tissue regeneration is unclear. Here, the authors use an ear punch assay in spiny mice, which regenerate fully, to show blastema formation and mesenchymal cell proliferation as cell cycle regulators p21 and p27 remain cytoplasmic.